2016
DOI: 10.3892/etm.2016.3268
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor inhibits CXCR4/SDF-1α signaling and overcomes stromal-mediated drug resistance in the HL-60 cell line

Abstract: Combining cytarabine, aclarubicin and granulocyte colony-stimulating factor (G-CSF) has demonstrated marked efficacy in the treatment of elderly and relapsed/refractory patients with acute myeloid leukemia (AML); however, the role of G-CSF remains poorly understood. The present study aimed to investigate the ability of G-CSF to overcome stromal-mediated drug resistance and the underlying molecular mechanism. Two types of co-culture models were established in the HS-5 human bone marrow/stromal and HL-60 human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
(34 reference statements)
2
12
1
Order By: Relevance
“…A very low level of miRNA-146a does not interfere with the signaling pathway of CXCR4/SDF-1 and enables efficient HSC adhesion in bone marrow niches. 28,50,51 The downregulated miRNA-223 expression observed between the conditioning treatment and day +7 after HSCT, as compared to the baseline, could have resulted from the significant decline in WBC or HSC progenitors and the inhibition of their differentiation. 34,36 The restricted expression of miRNA-223 in the early post-transplant period can be also explained by the inflammatory processes in HSC microenvironment after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A very low level of miRNA-146a does not interfere with the signaling pathway of CXCR4/SDF-1 and enables efficient HSC adhesion in bone marrow niches. 28,50,51 The downregulated miRNA-223 expression observed between the conditioning treatment and day +7 after HSCT, as compared to the baseline, could have resulted from the significant decline in WBC or HSC progenitors and the inhibition of their differentiation. 34,36 The restricted expression of miRNA-223 in the early post-transplant period can be also explained by the inflammatory processes in HSC microenvironment after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…28 Upregulated levels of miRNA-146a influence CXCR4 mRNA, which leads to slower HSC settling in bone marrow niches and consequently longer homing. 28 In the present study, we observed a correlation of miRNA-146a with MMP-9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNA-146a regulates mobilization of HSC as well as their homing after bone marrow transplantation [90][91][92][93]. Previous research has shown that under the influence of G-CSF, expression of CXCR4 chemokine receptor mRNA and protein in AML cells was decreased while the level of miRNA-146a was increased [94]. MiRNA-146a affects the CXCR4 mRNA, which leads to disruption of the SDF-1/ CXCR4 signaling pathway.…”
Section: Mirna-146amentioning
confidence: 99%
“…MiRNA-146a affects the CXCR4 mRNA, which leads to disruption of the SDF-1/ CXCR4 signaling pathway. It results in more efficient mobilization of HSCs, and slower homing [94]. Urocinase-type plasminogen activator receptor (uPAR), known to be modulated by miRNA-146a, by binding vitronectin is involved in extracellular matrix degradation, cell adhesion, and migration.…”
Section: Mirna-146amentioning
confidence: 99%